Alicja w Krainie Kognitywistyki - Rogulska, Anna (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The article comments on the ninth Polish translation of Lewis Carroll’s Alice in Wonderland, by Elżbieta Tabakowska. As the key to the analysis of this translation, the present author has chosen the relations between the text and image, especially the illustrations by sir John Tenniel and Tove Jansson. As opposed to previous translators or Alice in Wonderland, Tabakowska’s attempts to modernise the book to make it more accessible for 20th-century readers, and more compatible with 20th-century illustrations. In the edition discussed here, it is actually possible to discern two translations, translation proper and and an intersemiotic one, because illustrations by the author of Moomin books introduce connotations which would be totally alien to 19th-century girls. Through analysis of specific translation choices, the article underlines the strengths of the newest translation, such as its competent Polish, the wealth of Polish contexts, the educational role of exoticisation, and the retained principle of double reception. The article, however, also points out to certain weaknesses of the translation. Anna Rogulska also notices that, because the represented world is deeply rooted in the culture of Victorian England, the text cannot by fully rendered in the 21st century. Another interpretative key for the reading of the newest Polish edition of Carroll’s book is cognitive linguistics, which is the academic specialisation of the translator. The article demonstrates that the function of the new translation was not only a contribution to the long series of Polish renditions of Alice in Wonderland, but also a practical application of cognitive science in literature, which makes the translation valuable not only for children’s literature, but also for scientific inquiry.